A Lethal Twist - Case of Gastric Perforation Secondary to Gastric Volvulus - Priya, Surya; G, Gautham; Pandian A, Kumaresh; P, Surendran (Journal of Neonatal Surgery, 2025)
Gastric volvulus may be defined as an abnormal anterior or posterior rotation of part or almost all of the stomach about either the coronal or the sagittal axis of the body. The stomach, being fixed by the gastrophrenic ligaments above and by the peritoneum covering the second portion of the duodenum below, is limited in mobility between these fixed points only by the length of the lesser curvature and the length of the gastrohepatic omentum, and may be displaced within these limits by extrinsic pressure from whatever cause. This interesting condition is not of recent discovery, being first described by Berti in 1886, who found the condition at autopsy. Acute presentation of gastric volvulus is a rare condition with a high mortality for acute ischaemia. A 45-year-old female , homemaker with no notable past medical history presented to the emergency with history of generalized acute abdominal pain more over the right hypochondrium. . CECT abdomen revealed moderate volume of free fluid and air ( perihepatic and beneath anterior abdominal wall) with dependent air-fluid is seen within peritoneal cavity suggestive of gastric perforation. Twisting of stomach over it’s axial plane/ short axis is seen with gastro-esophageal junction seen below pyloro-duodenal junction, suggestive of gastric volvulus. Hence she was taken up for exploratory laparotomy with near total gastrectomy and gastrojejunostomy . Intraoperatively gastric perforation secondary to gastric volvulus with necrotic patch seen at the fundus of stomach anteriorly and body of stomach posteriorly . Postoperatively patient was kept NPO for 4 days . Gastrograffin study was done , revealed no anastomotic leak . Hence she was started on liquid diet gradually progressed to soft solids . Gastric volvulus is a rare surgical emergency which may become life-threatening if not treated timely. It is characterized by abnormal rotation of the stomach, causing vessel strangulation, ischemia or in some cases even perforation. Acute gastric volvulus is a surgical emergency with high morbidity and mortality. The most important factor in diagnosing acute volvulus of the stomach is a high index of suspicion. A constellation of clinical symptoms along with radiological studies helps in making the diagnosis. Emergency laparotomy is needed to prevent serious complications like gangrene and perforation